An Examination of Cultural Intelligence Changes of University Students Participating in Sport-Based Erasmus Plus Youth Projects - Hayri Demir; Sevket Cihat Özer (Türk Spor ve Egzersiz Dergisi)
This research aims to evaluate the changes in the cultural intelligence among those students who participate in Erasmus Plus Youth Projects based on sport. The group of the research consists of 39 students who study different departments in Nevşehir Hacı Bektaş Veli University and have not been abroad by any reason before. Cultural Intelligence Scale, developed by Ang et al. and adapted into Turkish by Gökhan Arastaman, has been implemented on the research group through a pre-test before their participation in the projects and a post-test after their participation in the project. For the analysis of the data collected during the research, SPSS 21.0 has been used. In the analysis of the data such descriptive statistics as arithmetic mean, frequency, standard deviation and percent values have been taken into consideration. Whether the data of the both scale distributed normally has been evaluated in order to determine if parametric analyses would be implemented. The research data have been observed to distribute normally. Accordingly, parametric analyses have been decided to be implemented to see if the data vary according to the demographic traits of the participants. T test has been implemented for the evaluation between two groups. Data of the analysis has revealed that participation in the Erasmus Plus Youth Project based on sport has a positive impact on the cultural intelligence, with all its subdimensions, of the university students.